2004
DOI: 10.1007/s00425-004-1321-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of tomato endo-?-1,4-glucanase Cel1 protein in fruit during ripening and after fungal infection

Abstract: The tomato (Lycopersicon esculentum Mill.) endo-beta-1,4-glucanase (EGase) Cel1 protein was characterized in fruit using specific antibodies. Two polypeptides ranging between 51 and 52 kDa were detected in the pericarp, and polypeptides ranging between 49 and 51 kDa were detected in locules. The polypeptides recognized by Cel1 antiserum in fruit are within the size range predicted for Cel1 protein and could be derived from heterogeneous glycosylation. Cel1 protein accumulation was examined throughout fruit rip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 36 publications
5
21
0
Order By: Relevance
“…Among the responses to B. cinerea shared by MG and RR fruit, expression of Cel1 (U13054), in the b-1,4-endoglucanase family, decreased 2-fold, confirming reports that the Cel1 protein is reduced when tomato leaves or fruit are inoculated with B. cinerea (Real et al, 2004;Flors et al, 2007).…”
Section: B Cinerea-inducible Gene Expression Changessupporting
confidence: 79%
“…Among the responses to B. cinerea shared by MG and RR fruit, expression of Cel1 (U13054), in the b-1,4-endoglucanase family, decreased 2-fold, confirming reports that the Cel1 protein is reduced when tomato leaves or fruit are inoculated with B. cinerea (Real et al, 2004;Flors et al, 2007).…”
Section: B Cinerea-inducible Gene Expression Changessupporting
confidence: 79%
“…CNR mRNA is up-regulated in fruit at the breaker stage [57], coincidently, our sequence results showed a negative correlation as expected. Two important targets of miR396 are endo-1, 4-beta-glucanase and MADS-box protein, both of which are important regulators in fruit ripening and softening [78,79]. Our sequencing results showed that the abundance of miR396 peaked at the breaker stage and decreased sharply in red ripening stage suggesting its possible function in fruit ripening.…”
Section: Discussionmentioning
confidence: 85%
“…, 1997). The Cel1 protein was also characterized in fruit and has several polypeptides (Real et al. , 2004), possibly as a result of variable amounts of either glycosylation at the potential N ‐glycosylation sites reported in the sequence analysis (Lashbrook et al.…”
Section: Introductionmentioning
confidence: 99%